2021
DOI: 10.3390/jcm10081639
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Training Depletes Antioxidant System but Does Not Affect Endothelial Functions in Women with Abdominal Obesity: A Randomized Trial with a Comparison to Endurance-Strength Training

Abstract: Limited data suggested that inclusion of a strength component into endurance exercises might intensify the beneficial effect of training. However, the available data is limited. Therefore, we aimed to compare the effect of endurance and endurance-strength training on anthropometric parameters, endothelial function, arterial stiffness, antioxidant status, and inflammatory markers in abdominally obese women without serious comorbidities. A total of 101 women were recruited and randomly divided into endurance (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…There were no statistically significant differences between groups at baseline.
Figure 1 CONSORT 2010 flow diagram 83 . The Figure was previously published in the Journal of Clinical Medicine which publishes articles under an open access Creative Common CC BY license.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no statistically significant differences between groups at baseline.
Figure 1 CONSORT 2010 flow diagram 83 . The Figure was previously published in the Journal of Clinical Medicine which publishes articles under an open access Creative Common CC BY license.
…”
Section: Resultsmentioning
confidence: 99%
“… CONSORT 2010 flow diagram 83 . The Figure was previously published in the Journal of Clinical Medicine which publishes articles under an open access Creative Common CC BY license.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, Jorge et al [52] reported that endurance training but not resistance and combined training increased the VO 2 peak. The lack of difference in the effect of endurance and endurance-strength training on physical capacity observed in our study can be partially explained by the similar volume and duration of the single training session for both types of programs as well as the similar impact of both types of training on anthropometric parameters [32].…”
Section: Discussionmentioning
confidence: 44%
“…Screening of the titles and abstracts excluded a further 33,344 articles and, therefore, 290 full texts were retrieved. Finally, 24 papers were included in the study [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], of which the two following papers related to the same study conducted on the same population and the same intervention but reported on the different outcomes: Nunes et al [ 47 ] and Martins et al [ 48 ]. Moreover, one manuscript was published in two journals [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, other studies have shown the opposite effect [ 21 , 22 ]. Moreover, some studies have observed an increase in IL-6 [ 23 , 24 ] and visfatin [ 25 ] levels after training programmes. In addition, the recent meta-analysis by Zheng et al [ 26 ] found that ET can effect a reduction in CRP, IL-6, and TNF-α in middle-aged and elderly people compared to a control group.…”
Section: Introductionmentioning
confidence: 99%